A national survey of anaesthetists (NAP5 Baseline) to estimate an annual incidence of accidental awareness during general anaesthesia in the UK. (11th March 2013) - Pandit, J. J.; Cook, T. M.; Jonker, W. R.; O'Sullivan, E.; ,
Summary As part of the 5th National Audit Project of the Royal College of Anaesthetists and the Association of Anaesthetists of Great Britain and Ireland concerning accidental awareness during general anaesthesia, we issued a questionnaire to every consultant and staff and associate specialist anaesthetist in the UK. The survey was designed to ascertain the number of new cases of accidental awareness that became known to them, for patients under their direct or supervised care, for a calendar year, and also to estimate how many cases they had experienced during their careers. The survey also asked about use of monitoring designed to measure the depth of anaesthesia. All local co‐ordinators responsible for each of 329 hospitals (organised into 265 'centres') in the UK responded, as did 7125 anaesthetists (82%). There were 153 new cases of accidental awareness notified to respondents in 2011, an estimated incidence of 1:15 414, lower than the 1–2:1000 previously reported in prospective clinical trials. Almost half the cases (72, 47%) occurred at or after induction of anaesthesia but before surgery, with 46 (30%) occurring during surgery and 35 (23%) after surgery before full recovery. Awareness during surgery appeared to lead more frequently to pain or distress than at induction and emergence (62% vs 28% and 23%, respectively). Depth of anaesthesia monitors were available in 164 centres (62%), but routinely used by only 132 (1.8%) of anaesthetists. The disparity between the incidence of awareness as notified to anaesthetists and that reported in trials warrants further examination and explanation.